Ferroptosis: emerging roles in lung cancer and potential implications in biological compounds - Liang, Qiuran; Wang, Yuehui; Li, Yili; Wang, Jinyan; Liu, Chuanbo; Li, Yicong (Frontiers in Pharmacology, 2024)
Lung cancer has high metastasis and drug resistance. The prognosis of lung cancer patients is poor and the patients' survival chances are easily neglected. Ferroptosis is a programmed cell death proposed in 2012, which differs from apoptosis, necrosis and autophagy. Ferroptosis is a novel type of regulated cell death which is driven by iron-dependent lipid peroxidation and subsequent plasma membrane ruptures. It has broad prospects in the field of tumor disease treatment. At present, multiple studies have shown that biological compounds can induce ferroptosis in lung cancer cells, which exhibits significant anti-cancer effects, and they have the advantages in high safety, minimal side effects, and less possibility to drug resistance. In this review, we summarize the biological compounds used for the treatment of lung cancer by focusing on ferroptosis and its mechanism. In addition, we systematically review the current research status of combining nanotechnology with biological compounds for tumor treatment, shed new light for targeting ferroptosis pathways and applying biological compounds-based therapies.